Algorithm development for acoustic emission measurement in high-frequency ranges and its application on a large two-stroke marine diesel engine. (1st October 2020) - Dong, Xuan Thin; Nguyen, Manh Hung; Lee, Donchool
Highlights: An advance measuring algorithm supports sampling rates up to 2MS/s and simultaneously measures on 8 channels. The number of display windows is flexible and depends on the number of input signals of each project. This algorithm is convenient and suitable for the measurements which require changes in the measuring place. It can record a large amount of data in a short time. The AE signal can be utilized to detect the firing state of the cylinder by using this algorithm. Abstract: In this paper, an advance measuring algorithm was designed to measure acoustic emission (AE) signals in a high-frequency range based on a C-Sharp programming language for a large two-stroke marine diesel engine. To verify the ability of this algorithm, an experiment was carried out to investigate the characteristics of the AE signal caused by the combustion process on the large two-stroke low-speed marine diesel engine in the frequency range 100–900 kHz. The results showed that the AE signals emitted from the combustion event at around the top dead center could be well-observed in this frequency range. These outcomes also proved that the AE signal could not propagate to other cylinders due to a big distance between the cylinders. However, the combustion process affected the remaining AE sources. Moreover, this technique could be applied to detect the firing state as well as the combustion time of each cylinder.